Prediction of Increase in House Prices Using Newton's Divided Difference Method - Hutapea, Risca Octaviyani; Sinaga, May Rani Tabitha; Lubis, Muhammad Shadri Ismaun; Aqil, Muhammad Fachri (Holistic Science, 2024)
This research predicts house price increases using Newton's Divided Difference Method based on historical datasets from the Melbourne Housing Snapshot (2016–2017). A pattern of rising home prices that is consistent with a linear trend is revealed by preliminary investigation. By building an interpolation polynomial using Newton's Divided Difference Method, home prices in 2025 are predicted to be AUD 1,753,391.53. This technique works well for spotting upward price trends in data that is continuously distributed linearly. These results offer crucial information to help with strategic choices in market research and real estate investing. This approach may accurately simulate the link between year (an independent variable) and house prices (a dependent variable) by using Newton polynomials. The impact of market demand and other economic factors on sharply rising property prices is reflected in these projections.